The Role of ADAM17 in PCOS Pathogenesis: A review Paper - Preap, Boren; Hong, Kimsor; Chen, Jianlin; Chen, Jingfei (Journal of Health Science and Medical Therapy, 2024)
This review primarily focuses on the Role of metalloproteinase (ADAM 17). Gynecological disease contributes to approximately 4.5% of the worldwide disease burden. Gynecological problems in women of reproductive age are linked to both In terms of diagnosis and treatment. Because there are no defined biomarkers, identifying gynecological disorders, particularly malignancies, has been difficult in most cases, and histopathological exams remained the gold benchmark. M.M.P.s, ADAMs, and ADAMTSs, as well as their endogenous inhibitors (TIMPs), influence the protease-dependent bioavailability of local niche components. ADAM 17 has been implicated in various pathological processes, including inflammatory response, cardiovascular disease, and, recently, ovarian dysfunction. Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age and is characterized by chronic anovulation, insulin resistance, and increased prevalence of cardiovascular risk factors. So far, the PCOS has not assessed the circulating levels of MMPs and their tissue inhibitors (TIMPs). This review will concentrate on the Role of (ADAM17) in regulating gynecological disorder (PCOS) and their consequent modulation for therapeutic intervention.